1994
DOI: 10.1590/s0004-282x1994000300001
|View full text |Cite
|
Sign up to set email alerts
|

Congruence of the topography of intracranial calcifications and epileptic foci

Abstract: SUMMARY -Nodular intracranial calcifications (NIC) are frequent findings in CT scans of epileptic patients in countries where granulomatous central nervous disease such as neurocysticercosis is endemic. In 34 consecutive epileptic patients with NIC submitted teo EEG, CT and CSF analysis, the correlation between the electroclinical localization of the focus and the topography of the NIC was studied. Twenty-nine patients had partial (Group I) and 5 had primarily generalized seizures (Group II). Twenty group I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
1
35
1
Order By: Relevance
“…This prevalence of bitemporal abnorm a l i t i e s i n c reases as the duration of the EEG re c o rdings increased. Other studies have also shown that surface EEG findings consisting of bilateral independent temporal foci, did not correlate with the effect of surgery in seizure's control 26,27 .…”
Section: Discussionmentioning
confidence: 93%
“…This prevalence of bitemporal abnorm a l i t i e s i n c reases as the duration of the EEG re c o rdings increased. Other studies have also shown that surface EEG findings consisting of bilateral independent temporal foci, did not correlate with the effect of surgery in seizure's control 26,27 .…”
Section: Discussionmentioning
confidence: 93%
“…For example, patients with severe refractory seizures may have only one calcified lesion and patients with multiple cysts or calcifications may have no seizures. Electroencephalography (EEG) has been found to be abnormal in 30% to 50% of patients with seizures due to NC and thus, EEG findings may have poor correlation with symptoms and CT lesions in patients with NC 37,38 . Discrepancies between clinical localization based on seizure semiology and location of the lesion on neuroimaging is not uncommon in patients with NC.…”
Section: Epileptogenesis Of Neurocysticercosis Lesionsmentioning
confidence: 99%
“…3 Seizures commonly occur in the presence of calcified granulomas [4][5][6][7][8][9] and are frequently localized to them. [10][11][12] Moreover, recurrent, transient episodes of perilesional edema (PEC) and enhancement, both maximally centered around the calcifications, have been described. 13,14 In a recent prospective study of patients with only calcified granulomas and a history of remote seizures, PEC was found in 50% of those patients with recurrent seizures and 8.7% of asymptomatic controls from the same population.…”
Section: Introductionmentioning
confidence: 99%